Leckéink a mezőgazdaság új rendje érdekében (Szociológiai Szemle, 2024)
The significant difference between the EU and the Hungarian agricultural structure cannot be eliminated. In the sense whether our agriculture has an agreeable structure, it should be seen that it is not conform to that of the EU. It may be an obstacle in the way of the branch getting support from the resources of the Common Agricultural Policy, preferring family farms. However, the difference does not hinder our accession, nor our integration if the question is approached in the sense whether our agriculture can be competitive under the conditions of market economy and Union membership. Therefore fitting the production system into the EU should not be done by forced transformation but setting out from the given situation and utilising its possibilities, it can be achieved by improving its ability to react amidst conditions of the market economy. Such an approach can also be harmonised with Union logic, according to which the existing, the operational „should be respected” .